Continuities and innovation in Luo song style: creating the Benga Beat in Kenya 1960 to 1995 - Eagleson, Ian (International Library of African Music, 2014)
Benga is a genre of guitar-band dance music in Kenya that first emerged within the Luo community during the late 1960s. Throughout its initial development among Luo bands and subsequent adaptation to several ethnic languages, benga provided many Kenyans with a malleable platform for enjoying a novel, emergent style that connected with the poetic and musical sensibilities of ethnic tradition that have been resilient in both rural and urban life. Each variant of benga expresses markers of its ethnic orientation, not only in the obvious sense of its language, but in concepts of rhythmic structure and melodic phrasing, tempo, form, and vocal timbre. They also present distinct developments in compositional identity initiated by various leading musicians. While these distinctions are obvious to benga musicians and fans, in scholarly and journalistic discussions of benga they are seldom discussed in a substantive way, and benga is often generalized as either a reflection of latent ethnic identities that persist in modern music, or a local derivative of Congolese music.
Keywords: African Music; Kenya; Benga Music; Benga Beat; Music of Congo